Peran Mahasiswa Magang di Balai Bahasa Sumatra Utara dalam Mengusulkan Lema Ke KBBI 6 Daring - Adiatullina Adiatullina; Junilia Ndruru; Menanti Simbolon; Nancy S. Simangunsong; Muharrina Harahap (Universitas Maritim AMNI Semarang, 2025)
Indonesian continues to evolve along with social, cultural, and technological dynamics, producing new vocabulary that requires systematic documentation. This research aims to identify the role of intern students at the Balai Bahasa Sumatra Utara in proposing entries for the 6th edition of the online Great Dictionary of the Indonesian Language (KBBI). Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. The research results show that interns made significant contributions to the lemma proposal process, which included data collection, linguistic analysis, and recommendation drafting. A total of 200 entries from the fields of physics, law, chemistry, and psychology were successfully proposed. The main findings include (1) a collaborative process between students, experts, and KBBI editors that supports the validity of lemmas; (2) contributions to the documentation of new scientific terms; and (3) challenges, such as limited reference sources and understanding of usage contexts. This research shows that the internship program not only contributes to the development of the Indonesian language but also provides practical learning experiences for students. Recommendations are provided for strengthening the internship system and optimizing the role of students in the management of the national language.